PENGARUH KUALITAS LAYANAN DAN PROMOSI PENJUALAN TERHADAP KEPUASAN KONSUMEN ALFAMART DI SUNTER - Lily Harjati (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2017)
High customer satisfaction will benefit companies because the company becomes efficient and effective, The more aware that the customer is an asset for the company. In general, the definition of Quality of Service is all forms of activities undertaken by the company to meet consumer expectations. Sales Promotion is an activity that is intended to help get consumers and awaken consumers to the existence of a company's products or services. Consumer Satisfaction is a perception evaluation of the difference between initial expectation and actual product performance as perceived after consuming product Theory used to support this research is definition along with indicators of service quality, sales promotion, and consumer satisfaction. The object of this research is consumers who are and have been shopping at Alfamart Sunter Jakarta. This study used questionnaires for data collection, while for sampling using non-probability sampling technique with accidentaly sampling technique (accidental selection). Data processed by using software SPSS 23. The results showed that (1) Quality of Service have a positive effect on Consumer Satisfaction (2) Sales Promotion has a positive effect on Consumer SatisfactionÂ Keywords: Servqual, Promotional Product, Customer Satisfaction